The story of the human body : evolution, health, and disease - Lieberman, Daniel E., 1964- (New York : Pantheon Books, 2013)
In this book the author, a Harvard evolutionary biologist presents an account of how the human body has evolved over millions of years, examining how an increasing disparity between the needs of Stone Age bodies and the realities of the modern world are fueling a paradox of greater longevity and chronic disease. It illuminates the major transformations that contributed key adaptations to the body: the rise of bipedalism; the shift to a non-fruit-based diet; the advent of hunting and gathering, leading to our superlative endurance athleticism; the development of a very large brain; and the incipience of cultural proficiencies. The author also elucidates how cultural evolution differs from biological evolution, and how our bodies were further transformed during the Agricultural and Industrial Revolutions. While these ongoing changes have brought about many benefits, they have also created conditions to which our bodies are not entirely adapted, the author argues, resulting in the growing incidence of obesity and new but avoidable diseases, such as type 2 diabetes. The author proposes that many of these chronic illnesses persist and in some cases are intensifying because of 'dysevolution,' a pernicious dynamic whereby only the symptoms rather than the causes of these maladies are treated. And finally, he advocates the use of evolutionary information to help nudge, push, and sometimes even compel us to create a more salubrious environment. -- From publisher's web site.
What are humans adapted for? -- Upstanding apes: how we became bipeds -- Much depends on dinner: how australopiths partly weaned us off fruit -- The first hunter-gatherers: how nearly modern bodies evolved in the human genus -- Energy in the ice age: how we evolved big brains along with large, fat, gradually growing bodies -- A very cultured species: how modern humans colonized the world with a combination of brains plus brawn -- Progress, mismatch, and dysevolution: the consequences-good and bad-of having paleolithic bodies in a post-paleolithic world -- Paradise lost?: the fruits and follies of becoming farmers -- Modern times, modern bodies: the paradox of human health in the industrial era -- The vicious circle of too much: why too much energy can make us sick -- Disuse: why we are losing it by not using it -- The hidden dangers of novelty and comfort: how everyday innovations can damage us -- Survival of the fitter: can evolutionary logic help cultivate a better future for the human body?
Includes bibliographical references and index.
Keywords: Human body; Human evolution; Adaptation (Biology); Hominidae -- physiology; Adaptation, Biological; Human Body